I recently learned that ...

\(\frac{1}{n(n+d)}\) = \(\frac{1}{d}(\frac{1}{n}-\frac{1}{n+d})\)

For example,

\(\frac{1}{3*5}=\frac{1}{3(3+2)}=\frac{1}{2}(\frac{1}{3}-\frac{1}{5})\)

Which is useful because we can use this equation in situation like this...

Find the value of \(\frac{1}{3*5}+\frac{1}{5*7}+\frac{1}{7*9}+\frac{1}{9*11}\)

\(=\frac{1}{2}(\frac{1}{3}-\frac{1}{5})+\frac{1}{2}(\frac{1}{5}-\frac{1}{7})+\frac{1}{2}(\frac{1}{7}-\frac{1}{9})+\frac{1}{2}(\frac{1}{9}-\frac{1}{11})\)

Take the common factor out

\(\frac{1}{2}[(\frac{1}{3}-\frac{1}{5})+(\frac{1}{5}-\frac{1}{7})+(\frac{1}{7}-\frac{1}{9})+(\frac{1}{9}-\frac{1}{11})]\)

The terms cancels each other and we are left with the first and last terms.

\(\frac{1}{2}[\frac{1}{3}-\frac{1}{11}]\)

which is \(\frac{4}{33}\) This way is MUCH faster than the traditional way

Anyone can prove why the equation i learned is true?

## Comments

Sort by:

TopNewest\( \dfrac{1}{n(n+d)} \)

\( = \dfrac{1}{d} \times \dfrac{d}{n(n+d)} \)

\( = \dfrac{1}{d} \times \dfrac{(n+d) - (n)}{n(n+d)} \)

\( = \dfrac{1}{d} \times \left(\dfrac{n+d}{n(n+d)} - \dfrac{n}{n(n+d)} \right) \)

\( = \dfrac{1}{d} \times \left( \dfrac{1}{n} - \dfrac{1}{n+d} \right) \) – Siddhartha Srivastava · 3 years, 6 months ago

Log in to reply

By using Partial Fractions,let - \( \frac{1}{n(n+d)} \) = \( \frac{A}{n} + \frac{B}{n+d} \)

Thus, we need to find the coefficients A and B. Therefore,by taking LCM,we get -

\( \frac{1}{n(n+d)} \) = \( \frac{A(n+d) + B \cdot n}{n(n+d)} \). Or, \( 1= n(A + B) + A \cdot d \)

Now, comparing the terms for different exponents of 'n' on both sides, we get-

{ This can be explained by example given below -

If ax + b = 3x +2 , then , a = 3 and b = 2 }

(Comparing the terms which contains \( n^0 \)on both sides),

\( n^0 : A \cdot d =1, or , A = \frac{1}{d} \)

(Comparing the terms which contains \( n^1 \) on both sides),

\( n^1 : A + B =0 , or, B = -A , \)

Or, \(B = \frac{-1}{d} \)

Therefore, \( \frac{1}{n(n+d)} \) = \( \frac{\frac{1}{d}}{n} + \frac{\frac{-1}{d}}{n+d} \)

\( \frac{1}{n(n+d)} \) = \( \frac{1}{d} ( \frac{1}{n} - \frac{1}{n+d}) \) – Rachit Mahendra · 3 years, 6 months ago

Log in to reply

– Peter Bishop · 3 years, 6 months ago

But i still don't understand the exponents of n part. Can you please explain futher.Log in to reply

It states the following: For any two polynomials \(P(x)=a_nx^n+a_{n-1}x^{n-1}+\cdots +a_1x+a_0\) and \(Q(x)=b_nx^n+b_{n-1}x^{n-1}+\cdots +b_1x+b_0\) such that \(P(x)=Q(x)\), then \(a_i=b_i\) for all \(i=0\to n\). – Daniel Liu · 3 years, 6 months ago

Log in to reply

– Peter Bishop · 3 years, 6 months ago

Awesome!!!!!!!!!!!!!!! Thank you very much.Log in to reply

Woah, cool bro! – Finn Hulse · 3 years, 6 months ago

Log in to reply

wow...good formula for rememberd – Ben Habeahan · 3 years, 6 months ago

Log in to reply

It's pretty easy.Multiply the RHS by \(n(n+d)\) and you will get \(\frac {1}{d}.[(n+d)-n]=1\) And that's it. – Bogdan Simeonov · 3 years, 6 months ago

Log in to reply

This method is use to solve many problems and is called telescoping method I think. – Anurag Pandey · 1 year, 1 month ago

Log in to reply

1/n(n+d) =1/d x d/n(n=d) =1/d x (n+d)-(n)/n(n+d) =1/d x {(n+d)/n(n+d-(n)/n(n+d)} =1/d x (1/n-1-n+d) HENCE PROVED – Nupur Ambani · 3 years, 6 months ago

Log in to reply

I just learnt A+B=0 so, A=-B wa0w. R I Newton yet? – Ayush Banerjee · 3 years, 6 months ago

Log in to reply

when we can write the pattern or series in the form that difference of two numbers and such that it get cancelled it makes the work easier this is called v n method or elemination method – Vignesh Subramanian · 3 years, 6 months ago

Log in to reply

Awesome method! From where did you get this?? – Nashita Rahman · 3 years, 6 months ago

Log in to reply

– Peter Bishop · 3 years, 6 months ago

From a tutorLog in to reply

Guys, if you like what you learnt, please reshare it so others can see. Thanks for the comments – Peter Bishop · 3 years, 6 months ago

Log in to reply